2023
DOI: 10.1007/jhep02(2023)210
|View full text |Cite
|
Sign up to set email alerts
|

How to identify different new neutrino oscillation physics scenarios at DUNE

Abstract: Next generation neutrino oscillation experiments are expected to measure the remaining oscillation parameters with very good precision. They will have unprecedented capabilities to search for new physics that modify oscillations. DUNE, with its broad band beam, good particle identification, and relatively high energies will provide an excellent environment to search for new physics. If deviations from the standard three-flavor oscillation picture are seen however, it is crucial to know which new physics scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 194 publications
(211 reference statements)
0
1
0
Order By: Relevance
“…In that case, a global analysis based on the neutrino oscillation and scattering data will affect the parameter space. Previously such analysis was performed mostly for the heavy mediator case (see for example [113][114][115][116][117][118][119]). A similar global analysis for the light scalar case will be very crucial to get bounds for a realistic light scalar model [108].…”
Section: Jhep03(2023)163mentioning
confidence: 99%
“…In that case, a global analysis based on the neutrino oscillation and scattering data will affect the parameter space. Previously such analysis was performed mostly for the heavy mediator case (see for example [113][114][115][116][117][118][119]). A similar global analysis for the light scalar case will be very crucial to get bounds for a realistic light scalar model [108].…”
Section: Jhep03(2023)163mentioning
confidence: 99%
“…This discrepancy could be an interesting hint toward new physics. Recent studies [24][25][26] have demonstrated that the presence of ò eμ and ò eτ , where ò eμ and ò eτ are the dimensionless parameters that quantify the non-standard interactions arising from e − μ and e − τ sector respectively, can help alleviate the tension between NOvA and T2K in the measurement of δ CP .…”
Section: Introductionmentioning
confidence: 99%
“…A study on how to identity new neutrino oscillation physics scenarios at DUNE experiment is presented in ref [35]…”
mentioning
confidence: 99%